La utilización de la expresión musical como estrategia para estimular el lenguaje oral en las niñas y niños del nivel inicial I de la escuela de educación básica Julio María Matovelle de la ciudad de Loja. Periodo 2014-2015 - Portilla León, Karen Gabriela (2016)
The title of this research is: USE OF MUSICAL EXPRESSION AS A STRATEGY TO ENCOURAGE ORAL LANGUAGE IN CHILDREN OF EARLY SCHOOL LEVEL I BASIC EDUCATION MARY JULY Matovelle LOJA CITY. PERIOD 2014-2015, where he was raised as a general objective: To determine the influence of musical expression as a strategy to stimulate oral language in children of the initial level I of the School of Education Basic Julio Maria Matovelle city of Loja . Period 2014 - 2015. This research was descriptive-correlational. The methods used in this study were: The descriptive, deductive and inductive analytical -sintético. The techniques and instruments were the survey, the same as the initial level teachers and instrument, the test CUMANIN the children on the initial level was applied I. The procedures were carried apply the appropriate permissions to managers school, for making the diagnosis and strategy; in primeria instance the problem through the test CUMANIN was diagnosed, then he worked with the strategy proposed for two weeks; and finally the retest was used to test the effectiveness of the strategy and progress in children / as. The research population was: 23 children (as) and 3 teachers of the initial level. It is concluded that: The musical expression contributed to the development of oral language of children from the School of Basic Education Julio Maria Matovelle city of Loja, because applying the CUMANIN test diagnosed only 9% were in an adequate level of articulatory language and improved after two weeks that the strategy was applied, and reached 39% at this level.